Rantai Distribusi Kopi Dalam Peningkatan Kesejahteraan Petani Di Kabupaten Ponorogo - Duwi Setyo Rahmawati; Hadi Sumarsono (JURNAL ILMIAH EDUNOMIKA, 2023)
Distribution chain is the relationship between distributor institutions or channeling institutions that have activities to distribute goods and services from producers to consumers. Distribution is one of the activities in the economy apart from production and consumption activities. Distribution activity is an activity to distribute or distribute goods or services from producers to consumers. Therefore, this study aims to analyze the coffee marketing distribution chain in Ponorogo Regency, in particular to determine the effect of marketing distribution techniques on the welfare of coffee plantation farmers. From this research it is known that the factor that determines the welfare of farmers is the right and correct marketing technique. Keywords : Coffee, Distribution Chain, Farmer welfare